POLITIK HUKUM MASA JABATAN KEPALA DAERAH HASIL PEMILIHAN KEPALA DAERAH SERENTAK 2020 BERDASARKAN PERSPEKTIF KEDAULATAN RAKYAT DI INDONESIA - Muhammad Haikal Diegio; Evi Deliana; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The main pillar in every democratic system is the existence of a mechanism forchanneling opinions by the people through periodic elections, Regional Head Elections(Pilkada) starting from Governors, Regents and Mayors are guaranteed in the constitution inArticle 18 Paragraph (4) of the Constitution of the Republic of Indonesia 1945, in Law No. 10 of2016 which basically regulates the end of the term of office of the Head of the 2020 ElectionResults Region, in his capacity the Head of the 2020 Election Results Region should be sworn infor a term of 5 (five) years since being appointed in accordance with Article 162 paragraph (2)of Law No. 10 of 2016 and Article 60 of Law No. 23 of 2014 so that the term of office should endin 2026, not ending the term of office until 2024 as contained in the provisions of Article 201paragraph (7) of Law No. 10 of 2016. Whereas referring to the provisions of Article 201paragraph (7) of Law No. 10 of 2016, regional heads and deputy regional heads as a result ofthe simultaneous local elections in 2020 will only serve 4 years, some may even be lacking due todelays in inauguration .This type of research can be classified as normative juridical research, because thisresearch is carried out by examining secondary data and approaches to laws, this normativeresearch examines the applicable regulations and relates them to legal politics in the formationof a rule to achieve legal policy ideas. in the implementation of the regional head's term of officeas a result of the 2020 regional head election, the data sources used are primary data, secondarydata, tertiary data, the data collection technique in this research is normative juridical, the dataused is library research.The results of this study examine and analyze the regulations currently in force, namelyLaw No. 10 of 2016 as a legal umbrella regarding terms of office for regional heads where thearrangements and contents of Law No. 10 of 2016 are not achieved which results in notachieving the goal of maintaining people's sovereignty, justice, and certainty by law as well ascertainty from within the law itself. the formation of the ideal law (ius constituendum) regardingthe regulation of the term of office of regional heads in the 2020 regional head election byregulating and establishing technical regulations that really regulate in detail the term of officeof regional heads to avoid a legal vacuum and abuse of office which undermines the system ofpeople's sovereignty in Indonesia.Keywords : Term of Office of Regional Heads, 2020 Simultaneous Regional Elections,LegalPolitics.